2020
DOI: 10.5334/jime.576
|View full text |Cite
|
Sign up to set email alerts
|

Social Justice and K-12 Teachers’ Effective Use of OER: A Cross-Cultural Comparison by Nations

Abstract: Open educational resources (OER) have the potential to promote social justice imperatives in education, but because of the uneven provision of technical infrastructure across different countries, it remains uncertain whether the people who need OER the most are its primary beneficiaries. In K-12 education, educators play a major role in the effort to incorporate OER into classroom teaching but, even if they are able to source such resources (overcoming the "first-level digital divide"), many lack the practical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…First, the research relied solely on data collected from participants in one class at the same institution in the United States. The cultural difference between different countries might also influence the interpretation of findings (Tang & Bao, 2020). Future research might consider validating the findings of this research in multiple research sites with a large sample of participants from various cultures.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…First, the research relied solely on data collected from participants in one class at the same institution in the United States. The cultural difference between different countries might also influence the interpretation of findings (Tang & Bao, 2020). Future research might consider validating the findings of this research in multiple research sites with a large sample of participants from various cultures.…”
Section: Discussionmentioning
confidence: 95%
“…Compared with traditional textbooks, open licensed textbooks are more likely to fulfill teachers' needs to provide differentiated instruction (Blomgren, 2018). In addition, research has indicated that classes that implement OER show no harm to course outcome and student motivation when they are compared to classes that use traditional textbooks (Lin & Tang, 2017;Tang & Bao, 2020). Therefore, advocating that K-12 teachers implement OER has become necessary for personalized instruction in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains uncertain whether the population in great needs for OER are the primary beneficiaries. For example, teachers in underdeveloped areas may not efficiently use or adapt OER due to the second-level digital divide in education (Tang and Bao 2020). This limits the capacity of OER in serving the targeted beneficiaries.…”
Section: Perspectives Beyond Efficacymentioning
confidence: 99%
“…This limits the capacity of OER in serving the targeted beneficiaries. On the other hand, underserved groups barely get their own voices heard in open education (Tang and Bao 2020). Educators from underserved groups should not simply translate the content in their local language and reuse it without considering whether to represent their voice and to fit local contexts (Hodgkinson-Williams and Trotter 2018).…”
Section: Perspectives Beyond Efficacymentioning
confidence: 99%
“…There was unequal access to technology that gave some students advantages over others. However, current data suggests that the divide has shifted (Hall et al, 2020;Kaden, 2020;Lynch, 2020;Reinhart et al, 2011;Sandvik, 2020;Tang & Bao, 2020). Even when access to technology is equal, inequities persist because some students and teachers do it highlighted digital divide issues, but lessons learned should be carried over to benefit students and achieve educational equity (Hall et al, 2020).…”
Section: Introductionmentioning
confidence: 99%